Abundance, richness and composition of lianas in forest communities along an elevation gradient in New Caledonia. (2nd November 2017) - Bruy, David; Ibanez, Thomas; Munzinger, Jérôme; Isnard, Sandrine
Abstract : Background : Lianas are an abundantand dynamic component of tropical forests, and their abundance ispredicted to increase with global change. A better understandingof factors that explain their distribution is required, especially onoceanic islands for which few data are available. Aims : Identifythe environmental factors that shape liana communities in NewCaledonian forests Methods : We studied liana abundance, basal area, richness and climbing modes in 27 forest plots (20m × 20 m) along an elevation gradient (sea level to ca. 1000 ma.s.l.) that covers different forest types and precipitation regimes. Results : We inventoried 992 lianas belonging to 71 species. The abundance and basal area decreased logarithmically withincreasing elevation while species richness tended to peak at midelevations.Twining lianas were the most abundant and species-richfunctional group. We found no clear relationship between climbingmodes and forest structure. Conclusions : Our results show thatliana abundance decreases with increasing elevation in responseto lower precipitation in seasonal dry forest. At high elevation (600–1000 m a.s.l.), climbing secondary hemi-epiphytes replace lianasprobably as a result of climate-based niche differentiation. Variationof species richness along the gradient could not be explained byprecipitation or by forest structural parameters.